Tryptophan moiety ligand based tri/tetranuclear Ni(ii) complexes: syntheses, structure and magnetic properties - Mahish, Manas Kumar; Carrella, Luca M.; Patra, Apu; Saren, Dama; Zangrando, Ennio; Vojtisek, Pavel; Rentschler, Eva; Manna, Subal Chandra (New Journal of Chemistry, 2022)
Tetra/trinuclear Ni(ii) complexes, namely [Ni4(l)4(H2O)4]·5(dmf)·7(H2O) (1) and [Ni3(l)2(bz)2(dmf)2(H2O)2] (2) [H2L = N-(2-(hydroxy)-3-methoxybenzylidene)tryptophan); dmf = dimethyl formamide, bz = benzoate anion], have been synthesized and characterized by X-ray single crystal structure determination. The structural characterization discloses a tetranuclear Ni(ii) complex for 1, whereas in complex 2 the competition between the coordination ability of the benzoate anion and the bridging mode of the Schiff base leads to a trinuclear species. Two of the chiral ligands in 1, acting as pentadentate, connect all metal centers, while the other two act as tri-chelating towards the side located nickel centers. On the other hand, in complex 2 the two Schiff bases act as tetradentate connecting the nickel centers in pairs in addition to the benzoate anions. Variable-temperature magnetic susceptibility data, collected in the temperature range of 2-300 K under an applied field of 0.1 Tesla, indicate weak antiferromagnetic interactions in both the complexes in agreement with Ni-O-Ni bridging angles larger than 100° measured within the molecular structures.
CRIS-Team Scopus Importer:2023-03-27